CLINICAL SIGNIFICANCE OF ANEMIC SYNDROME IN PATIENTS WITH CHRONIC HEART FAILURE - V. N. Larina; B. Ya. Bart; V. G. Larin (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the anemia prevalence and its impact on chronic heart failure (CHF) course.Methods. A total of 228 outpatients (86 women and 196 men, aged 39-85 y.o.) with clinically stable CHF (II-IV functional class according to NYHA) were studied. Anemia was defined by the WHO criteria (hemoglobin levels <13 g/dl in men and <12 g/dl in women).Results. Anemia was found in 18,8% of CHF patients. In all the cases anemia was mild (hemoglobin levels >9 g/dl). Anemia rate did not differ significantly in patients with reduced (18,5%) and preserve (19,1%) or left ventricle ejection fraction (LV EF) (р=0,743). Anemic and non anemic patients were similar in terms of gender, NYHA functional class, heart rate and LV EF. The rate of anemic patients increased significantly up to 35,8% in creatinine clearance <60ml/min. Anemic patients were older (p<0,001), had longer CHF duration (p=0,014), lower body mass index (p=0,041), had diabetes more often (p=0,004, χ2=8,01) in comparison with non anemic patients. Deficiency of iron, vitamin B12 or folic acid was a reason of anemia in 35,8%, 9,4% and 15,1% of patients, respectively. Anemia reason was not detected in 39,7% of patients.Conclusion. Anemia in patients with CHF is associated with age, impaired renal function, diabetes and high hospitalization rate because of CHF deterioration.